Evolution of User Authentication Methods in Mobile Phones: A Security Perspective - Ooi Yee Hui, Deborah; Kian Yuen, Kok; Asha Farina Binti Shikh Mohd Zahor, Bibi; Lim Ching Wei, Kelvin; Fitri Zaaba, Zarul; Rajab Asaad, Renas (International Journal of Engineering and Technology, 2018)
There are many ways of performing user authentication in mobile phones. Back then, a specific button is assigned as a security lock button such as the asterisk yet major concerns on security issues over personal data stored in mobile phones have been raised. Password-based authentication took over the trend with pattern and PIN unlock being commonly used by users of mobile phones. However, these methods are still prone to fraud as unethical users tend to break the passcode using shoulder surfing or hacking. To further strengthen the security in mobile phones, biometric authentication approaches are proposed. In this paper, four biometric-based authentication methods are being compared through a several aspects. As a result, the most significant biometric-based authentication approach is presented.